Botulinum Toxins Type A (Bont-A) in the Management of Lower Limb Spasticity in Children: A Systematic Literature Review and Bayesian Network Meta-analysis. (June 2019) - Guyot, Patricia; Kalyvas, Chrysostomos; Mamane, Carole; Danchenko, Natalya
Background: Botulinum neurotoxins type A (BoNT-As) are used in pediatric lower limb spasticity, which affects more than 2.5 million children worldwide. Botulinum neurotoxins type-A improve active function and delay musculoskeletal complications. The objective of this analysis was to evaluate the efficacy and safety of abobotulinumtoxinA versus other botulinum neurotoxins type A in pediatric spasticity, in the absence of head-to-head evidence. Methods: A systematic literature review was conducted to identify relevant randomized controlled trials. The evidence base was synthesized with Bayesian network meta-analyses. Outcomes analyzed included Modified Ashworth Scale, Tardieu Scale (TS) spasticity grade, and Goal Attainment Scale (standard mean difference only) at 12 weeks postinjection, and adverse events occurring during study periods. Results: Thirty-eight studies were identified, 10 of which met inclusion criteria for quantitative synthesis. On Modified Ashworth Scale, abobotulinumtoxinA 15 U/kg/leg was significantly more efficacious than onabotulinumtoxinA 4 U/kg/leg (–0.99 [–1.34, –0.64]) and onabotulinumtoxinA 4 U/kg/leg+casting (–0.81 [–1.16, –0.46]) and numerically better than onabotulinumtoxinA 8 U/kg (–0.40 [–0.67, –0.14]). AbobotulinumtoxinA 10 U/kg/leg was significantly more efficacious than onabotulinumtoxinA 4 U/kg/leg (±casting). On Goal Attainment Scale, abobotulinumtoxinA 15 U/kg/leg and 10 U/kg/leg were significantly more efficacious than onabotulinumtoxinA 12 U/kg/leg. On Tardieu Scale spasticity grade, abobotulinumtoxinA was comparable to other treatments. AbobotulinumtoxinA demonstrated adverse event rates comparable to all doses of onabotulinumtoxinA. Conclusions: In pediatric lower limb spasticity, abobotulinumtoxinA offered significant or numerical efficacy advantages on tone (Modified Ashworth Scale) and functional outcomes (Goal Attainment Scale), and comparable efficacy on Tardieu Scale spasticity grade. AbobotulinumtoxinA was comparable to onabotulinumtoxinA on tolerability. Results should be interpreted in the context of heterogeneity and sparsity of the evidence base.